Corrosion-resistant waterstop and preparation method thereof
By optimizing the material formulation and preparation process, the coordinated corrosion protection barrier and gradient filler network of ethylene propylene rubber and neoprene are adopted, and combined with accelerators to regulate sulfur crosslinking, the problem of insufficient corrosion resistance of the water stop belt in complex environments is solved, and the effects of high strength, durability and waterproof sealing are achieved.
Patent Information
- Application Number
- CN202510776550.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-08-12
- Estimated Expiration
- 2045-06-11
AI Technical Summary
The existing water stops have insufficient corrosion resistance in complex environments, resulting in a degradation of structural performance, affecting the safety and reliability of buildings, tunnels and chemical facilities.
The dual-phase anti-corrosion barrier is used to jointly build an ethylene propylene rubber and neoprene rubber, and the gradient filling network of white carbon black and calcium carbonate is combined. The sulfur cross-linking is accurately regulated using accelerator to form a high-density and uniform sulfur bond network structure, and the stability of the material in a corrosive environment is ensured through the optimization of the mixing and vulcanization process.
Significantly improve corrosion resistance, extend the service life of the water stop belt in corrosive environment, maintain excellent mechanical properties, avoid seal failure, and improve material reliability and durability.
Smart Images

Figure CN120464094A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer compound composition waterstops, and in particular to a corrosion-resistant waterstop and a preparation method thereof. Background Art
[0002] Waterstops play a crucial role in waterproofing and sealing in expansion joints of construction projects, tunnel joints, joints in hydraulic engineering projects, and joints in chemical facilities. However, existing waterstops still have many problems in practical applications.
[0003] Traditional waterstops are primarily made of rubber materials, such as natural rubber and nitrile rubber. While these materials offer a certain degree of elasticity and sealing, they lack corrosion resistance. Under complex environmental conditions, such as long-term contact with groundwater, acidic and alkaline substances in the soil, and corrosive media in chemical facilities, waterstops are susceptible to aging and corrosion. This can lead to a decline in structural performance, cracks, and deformation, compromising waterstop effectiveness and potentially creating leakage risks.
[0004] In construction projects, corrosion of expansion joint waterstops not only causes internal dampness and damage, impacting the building's service life, but can also lead to serious structural safety issues. In tunnel projects, corrosion of waterstops can cause water seepage into the tunnel walls, compromising its normal operation and safety. In water conservancy projects, failure of waterstops can lead to waste of water resources, damage to water conservancy facilities, and even disasters such as floods. In chemical facilities, corrosion of waterstops can cause chemical leaks, resulting in environmental pollution and safety accidents, bringing significant economic losses and social harm.
[0005] Furthermore, existing waterstop manufacturing processes have limitations in improving the material's corrosion resistance. Inadequate raw material processing during the manufacturing process prevents the synergistic effects of various components from being fully utilized to enhance corrosion resistance. Furthermore, insufficient optimization of key process parameters, such as vulcanization, prevents the rubber molecules from fully cross-linking to form a dense protective structure, thus failing to effectively resist erosion by corrosive substances.
[0006] In summary, the development of a waterstop with excellent corrosion resistance and its preparation method has important practical significance for ensuring the safe and reliable operation of construction projects, tunnels, water conservancy projects and chemical facilities. Summary of the Invention
[0007] The present invention aims to solve the problem of insufficient corrosion resistance of existing waterstops. By optimizing the material formula and preparation process, a waterstop with excellent corrosion resistance in complex environments and a preparation method thereof are provided to meet the waterproofing and sealing needs in fields such as construction projects, tunnels, water conservancy projects and chemical facilities.
[0008] To achieve the above object, the technical solution adopted by the present invention is: a corrosion-resistant waterstop, composed of the following raw materials in parts by mass: 50-70 parts of EPDM rubber, 20-40 parts of chloroprene rubber, 3-8 parts of zinc oxide, 1-3 parts of stearic acid, 1-2 parts of antioxidant, 5-15 parts of paraffin oil, 20-40 parts of white carbon black, 30-50 parts of calcium carbonate, 1.5-3 parts of sulfur, and 0.5-1.5 parts of accelerator; The accelerator has a structure shown in Formula 1: Formula 1; The Z1 is selected from the group consisting of: O, S, C(CH3)(CH3), and NH.
[0009] Furthermore, the ethylene content of the EPDM rubber is 50-60 wt %, and the Mooney viscosity [ML (1+4) 125° C.] is 50-70.
[0010] Furthermore, the chloroprene rubber is CR122 type chloroprene rubber.
[0011] Furthermore, the antioxidant is N-isopropyl-N , -phenyl-p-phenylenediamine and / or N-(1,3-dimethylbutyl)-N , -phenyl-p-phenylenediamine.
[0012] Further, the N-isopropyl-N , -The structure of phenyl-p-phenylenediamine is: .
[0013] Furthermore, the N-(1,3-dimethylbutyl)-N , -The structure of phenyl-p-phenylenediamine is: .
[0014] Furthermore, the promoter is any one of the compounds shown in the following structures: .
[0015] Furthermore, the synthesis method of the accelerator is: ; Step 1: Raw materials 1 and 2 are subjected to substitution reaction to synthesize intermediate 1; Step 2: Intermediate 2 is synthesized by Buchwald-Hartwig arylation reaction of intermediate 1 and raw material 3; Step 3: The intermediate 2 and the raw material 4 are subjected to Buchwald-Hartwig arylation reaction to synthesize the promoter.
[0016] A method for preparing a corrosion-resistant waterstop comprises the following steps: S1. The EPDM rubber, chloroprene rubber, zinc oxide, stearic acid and antioxidant were added to an internal mixer and mixed at 80-100 ° C for 3-5 minutes to obtain material A; S2. Add the paraffin oil, white carbon black and calcium carbonate to the material A, raise the temperature to 120-140 ° C and mix for 8-12 minutes to obtain material B; S3. The material B was transferred to an open mill, the sulfur and accelerator were added, and the mixture was thinly passed 3-5 times at 40-60 ° C to obtain a rubber mix; S4. The rubber mixture is placed in a mold, vulcanized in a vulcanizer at 160-180°C and 10-20 MPa for 10-30 minutes, placed in an oven at 70-80°C for 2-4 hours, and cooled to room temperature to obtain a corrosion-resistant waterstop.
[0017] Furthermore, the mixing process of S1 and S2 is carried out under the protection of inert gas.
[0018] Furthermore, the vulcanization temperature is 165-175° C., and the vulcanization time is 15-25 minutes.
[0019] Furthermore, the number of thin passes is 4 times, and the roller spacing of the mixing mill is 0.5-1.0 mm.
[0020] The invention discloses an application of a corrosion-resistant waterstop in waterproof sealing of expansion joints in construction projects, tunnel joints, water conservancy project joints or chemical facility joints.
[0021] The accelerator described in the present invention is used in rubber processing. Sulfur is a vulcanizing agent, but when sulfur acts alone, the reaction rate is slow and the efficiency is low. The accelerator accelerates the cross-linking reaction between sulfur and rubber molecules. Through the action of the accelerator, the rubber molecular chain can form a denser and more uniform cross-linked network in a shorter time and with lower energy consumption. This structure is the basis for the rubber to have high strength, elasticity and resistance to medium corrosion. The accelerator of the present invention forms a denser protective barrier for the rubber by improving the cross-linking density and uniformity, thereby reducing the diffusion of corrosive media into the interior of the material, delaying swelling and aging, and maintaining long-term sealing performance (especially in corrosive environments such as chemical facilities and water conservancy projects). The accelerator optimizes the vulcanization efficiency, ensures that the antioxidant is evenly dispersed in the cross-linked network, maximizes its anti-aging effect, and further extends the life of the waterstop in a corrosive environment.
[0022] The present invention constructs a two-phase anti-corrosion barrier through the polar-nonpolar synergy of EPDM and chloroprene rubber: EPDM provides an inert matrix resistant to ozone / acid and alkali corrosion, while the chlorine-containing structure of CR122 chloroprene rubber imparts oil resistance and stability to polar media. On this matrix, silica and calcium carbonate form a gradient filling network—silica enhances crosslinking density, while calcium carbonate fills microscopic voids, synergistically reducing the permeability of corrosive media. In the core additive system, the dual active centers of the accelerator precisely regulate sulfur crosslinking, forming a high-density, uniform sulfur bond network that physically blocks corrosion diffusion; at the same time, they work in synergy with antioxidants to ensure that the anti-aging components are evenly dispersed in the crosslinked skeleton, effectively inhibiting oxidative degradation over the long term. In the preparation process, segmented mixing is carried out under an inert atmosphere to ensure uniform dispersion of components and avoid high-temperature oxidation; low-temperature thin-pass and precise vulcanization optimize the cross-linking dynamics, so that the rubber molecules form a dense three-dimensional network; post-heat treatment eliminates internal stress, and finally obtains a corrosion-resistant sealing structure with high cross-linking density, low defect rate and long-term anti-aging, which significantly reduces the swelling rate and extends the service life.
[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. Significantly improve corrosion resistance: By optimizing the rubber matrix (EPDM rubber and chloroprene rubber in collaboration) and filler system (silica / calcium carbonate gradient filling), a denser anti-permeability barrier is formed, effectively resisting the erosion of acid and alkali media, oils and chemical corrosive substances, and extending the service life of the waterstop in corrosive environments.
[0024] 2. Enhanced mechanical property stability: The new accelerator precisely regulates the sulfur cross-linking process to form a high-density and uniform sulfur bond network structure, enabling the material to maintain excellent mechanical properties such as tensile strength and elongation at break in a corrosive environment, thus avoiding sealing failure caused by swelling or aging.
[0025] 3. Optimize the synergy between process and performance: The combination of segmented mixing (inert gas protection), low-temperature thin-pass and precise vulcanization process ensures that the components are evenly dispersed and forms a low-defect cross-linked network; post-heat treatment further eliminates internal stress, makes the material structure more stable, and comprehensively improves the reliability and durability of the waterstop. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 For the accelerator 1 of the present invention 1 HNMR spectrum.
[0027] Figure 2 The invention provides a method for synthesizing the accelerator. DETAILED DESCRIPTION
[0028] The following will clearly and completely describe the technical solution of the present invention in conjunction with the accompanying drawings. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0029] Synthesis example 1 Synthesis of accelerator 1: ; Step 1: Under a nitrogen atmosphere, 20 g of raw material 1, 21.67 g of aluminum chloride, and 150 g of toluene were added sequentially to the reaction system. After stirring and mixing, the system temperature was lowered to -20°C and a 50 ml toluene solution containing 12.73 g of raw material 2 was added dropwise. The temperature was raised to room temperature and the reaction was allowed to react for 6 h. After the reaction, the pH of the system was adjusted to neutral with 0.1 mol / L aqueous hydrochloric acid. 200 g of water was added, the reaction mixture was shaken, allowed to stand, and the liquids separated. The organic phase was retained, dried, and subjected to column chromatography using a mixture of petroleum ether and dichloromethane as the eluent to obtain 20.60 g of intermediate 1. MS [MS+1]: 339.
[0030] Step 2: Under a nitrogen atmosphere, 20.60 g of Intermediate 1, 20.81 g of Raw Material 3, 1.66 g of tris(dibenzylideneacetone)dipalladium, 16.74 g of potassium carbonate, 0.6 g of tri-tert-butylphosphine, and 210 g of toluene were added sequentially to the reaction system. The temperature was raised to 120° C. and refluxed for 12 h. After the reaction, the temperature was slightly lowered and the mixture was filtered through diatomaceous earth to remove salts and the catalyst. The filtrate was cooled to room temperature and washed three times with water. The organic phase was retained and the aqueous phase was extracted with ethyl acetate. The organic phases were combined, dried over anhydrous magnesium sulfate, spin-dried, and subjected to silica gel column chromatography using a mixture of petroleum ether and ethyl acetate as the eluent to obtain 21.18 g of Intermediate 2. MS [MS+1]: 546.
[0031] Step 3: Under a nitrogen atmosphere, 21.18 g of intermediate 2, 13.66 g of raw material 4, 1.07 g of tris(dibenzylideneacetone)dipalladium, 10.72 g of potassium carbonate, 0.4 g of tri-tert-butylphosphine and 220 g of toluene were added to the reaction system in sequence, the temperature was raised to 120 ° C, and the reaction was refluxed for 12 hours; after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and the aqueous phase was then extracted with ethyl acetate; after the organic phases were combined, they were dried over anhydrous magnesium sulfate, spin-dried, and subjected to silica gel column chromatography using a mixture of petroleum ether and ethyl acetate as eluent to obtain 23.08 g of promoter 1.
[0032] Final product structure identification: MS of accelerator 1 [MS+1]: 758; Accelerator 1 1 HNMR-deuterated chloroform- Figure 1 : δ8.63-8.56(m,1H),7.90(m,1H),7.86-7.73(m,5H),7.72-7.52(m,3H),7.27-7.19(m,1H),6.95(dd,1H),6.77(dd,1H) ,5.24(dd,1H),5.15(dd,1H),4.88(m,1H),4.61(t,3H),3.80(d,6H),2.62(m,1H),2.41(m,1H),0.87(s,9),0.10(s,6H).
[0033] Synthesis Example 2-Synthesis Example 4 Accelerators 2 to 4 were synthesized sequentially using the same method as in Synthesis Example 1, except that Raw Material 2 was substituted. The structures of Raw Material 2, Accelerators 2 to 4, and MS [MS+1] data are shown in the table below.
[0034]
[0035] Example 1 Preparation of a corrosion-resistant waterstop: Raw material composition: EPDM rubber: 60 parts (ethylene content 55wt%, Mooney viscosity [ML(1+4)125℃] 60), chloroprene rubber: 30 parts (CR122 type), zinc oxide: 5 parts, stearic acid: 2 parts, antioxidant: 1.5 parts (N-(1,3-dimethylbutyl)-N , -phenyl-p-phenylenediamine), paraffin oil: 10 parts, white carbon black: 30 parts, calcium carbonate: 40 parts, sulfur: 2 parts, accelerator: 1 part (accelerator 1 prepared in Synthesis Example 1 is selected).
[0036] Preparation method: S1. Add EPDM rubber, chloroprene rubber, zinc oxide, stearic acid, and antioxidant into an internal mixer and mix at 90°C for 4 minutes under nitrogen protection to obtain material A.
[0037] S2. Add paraffin oil, white carbon black, and calcium carbonate to material A, raise the temperature to 130°C under nitrogen protection and mix for 10 minutes to obtain material B.
[0038] S3. Transfer material B to an open mill (roller spacing 0.8 mm), add sulfur and accelerator 1, and pass through the mill at 50°C for 4 times to obtain a rubber mix.
[0039] S4. The rubber mix was placed in a mold and vulcanized in a vulcanizer at 170°C and 15 MPa for 20 minutes. The mixture was then heat-treated in an oven at 75°C for 3 hours and cooled to room temperature to obtain a corrosion-resistant waterstop.
[0040] Example 2-Example 4 A corrosion-resistant waterstop is prepared by referring to the preparation method of Example 1, wherein the accelerator is replaced with the accelerator prepared in Synthesis Example 2 to Synthesis Example 4 in sequence, and the rest remains the same as Example 1.
[0041] Comparative Example 1 A corrosion-resistant waterstop is prepared by referring to the preparation method of Example 1, except that the accelerator is replaced by comparative compound 1, and the rest remains the same as Example 1.
[0042] Comparative compound 1: .
[0043] Comparative Example 2 A corrosion-resistant waterstop is prepared by referring to the preparation method of Example 1, without adding the accelerator, and the rest remains the same as Example 1.
[0044] Performance testing: Cut the waterstop (an aging-resistant waterstop prepared in the examples and comparative examples) into dumbbell-shaped specimens of equal size according to the method specified in GB / T9865.1 and soak them in a 0.2 mol / L hydrochloric acid aqueous solution for 4 hours. The tensile stress-strain properties of the waterstop were measured in accordance with GBT528-1998. On a tensile testing machine moving at a constant speed, the dumbbell-shaped waterstop specimens were evenly placed on the upper and lower clamps, stretched, and the testing machine was started for testing. The higher the tensile strength, tensile strength at break, and elongation at break, the better the corrosion resistance.
[0045]
[0046] The embodiment group using the specific accelerator of the present invention showed an overall superior ability to maintain mechanical properties in an acid corrosion environment, and its tensile strength and elongation at break were systematically significantly higher than those of the traditional accelerator control group and the no-accelerator group. Accelerators with different heteroatom structures have a slight gradient effect on performance, among which the accelerator containing N / O is slightly better than the variant containing S / C, which confirms the structure-activity relationship between molecular design and anti-corrosion performance. What is particularly critical is that the performance of the control group showed a cliff-like decline, especially the comparative example 2, which caused serious degradation of the material structure due to insufficient vulcanization, fully verifying the necessity of high-efficiency accelerators for building a dense cross-linked network. The overall trend proves that the synergistic effect of the EPDM / chloroprene rubber matrix, gradient filler and new accelerator successfully achieved the strengthening of the anti-penetration corrosion barrier, fundamentally solving the technical defect that the existing waterstop is prone to failure in corrosive media.
[0047] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A corrosion-resistant waterstop, characterized in that: The invention is composed of the following raw materials in parts by mass: 50-70 parts of EPDM rubber, 20-40 parts of chloroprene rubber, 3-8 parts of zinc oxide, 1-3 parts of stearic acid, 1-2 parts of antioxidant, 5-15 parts of paraffin oil, 20-40 parts of white carbon black, 30-50 parts of calcium carbonate, 1.5-3 parts of sulfur, and 0.5-1.5 parts of accelerator; The accelerator has a structure shown in Formula 1: Formula 1; The Z1 is selected from the group consisting of: O, S, C(CH3)(CH3), and NH.
2. A corrosion-resistant waterstop according to claim 1, characterized in that: The ethylene content of the EPDM rubber is 50-60 wt %, and the Mooney viscosity [ML (1+4) 125° C.] is 50-70.
3. A corrosion-resistant waterstop according to claim 1, characterized in that: The chloroprene rubber is CR122 type chloroprene rubber.
4. A corrosion-resistant waterstop according to claim 1, characterized in that: The antioxidant is N-isopropyl-N , -phenyl-p-phenylenediamine and / or N-(1,3-dimethylbutyl)-N , -phenyl-p-phenylenediamine.
5. The corrosion-resistant waterstop according to claim 1, characterized in that: The accelerator is any one of the compounds shown in the following structures: 。 6. A method for preparing a corrosion-resistant waterstop according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. The EPDM rubber, chloroprene rubber, zinc oxide, stearic acid and antioxidant were added to an internal mixer and mixed at 80-100 ° C for 3-5 minutes to obtain material A; S2. Add the paraffin oil, white carbon black, and calcium carbonate to the material A, raise the temperature to 120-140 ° C and mix for 8-12 minutes to obtain material B; S3. The material B was transferred to an open mill, the sulfur and accelerator were added, and the mixture was thinly passed 3-5 times at 40-60 ° C to obtain a rubber mix; S4. The rubber mixture is placed in a mold, vulcanized in a vulcanizer at 160-180°C and 10-20 MPa for 10-30 minutes, placed in an oven at 70-80°C for 2-4 hours, and cooled to room temperature to obtain a corrosion-resistant waterstop.
7. The method for preparing a corrosion-resistant waterstop according to claim 6, characterized in that: The mixing process of S1 and S2 is carried out under the protection of inert gas.
8. The method for preparing a corrosion-resistant waterstop according to claim 6, characterized in that: The vulcanization temperature is 165-175° C., and the vulcanization time is 15-25 minutes.
9. The method for preparing a corrosion-resistant waterstop according to claim 6, characterized in that: The number of thin passes is 4 times, and the spacing between the rollers of the mixing mill is 0.5-1.0 mm.
10. Use of the corrosion-resistant waterstop according to any one of claims 1 to 5 in waterproof sealing of expansion joints in construction projects, tunnel joints, water conservancy project joints or chemical facility joints.
Citation Information
Patent Citations
Steel-edged water stop and preparation method thereof
CN105647024A
Benzothiazole sulfamino low-volatile sulfur-containing silane coupling agent and synthesis method thereof
CN111320782A
Piston returning assembly and caliper assembly including thereof
KR1020250062102A
Method of oxidizing an alcohol using a recyclable fluorous sulfoxide
US20030105363A1
Cited By
Waterproof and anti-corrosion waterstop for construction joint and preparation method of waterproof and anti-corrosion waterstop
CN122080538A